Effective Recommendation Considering Customers’ Needs Using Review Texts with TF-IDF and Word2Vec: Case of Golf Course - Kodai Kimura; Takashi Namatame (Advances in Technology Innovation, 2025)
This paper aims to recommend the most suitable golf course for each user by focusing on golf courses and analyzing customer reviews. Furthermore, by examining the recommendation results, the goal is to clarify the characteristics of each golf course from the user’s perspective and contribute to the promotion of each golf course. The procedure of this paper is first to extract user preferences using Word2vec and TF-IDF from reviews. Next, the extracted user preferences are matched with golf course features. Finally, recommendations are made based on the geographical relationship between the user and the golf course. As a result, a high accuracy rate is achieved. Additionally, some keywords that should be used in promotions for each golf course feature have been identified.